STORYTELLING AS AN EFFECTIVE TECHNOLOGY FOR TEACHING THE COURSE «LEADERSHIP IN EDUCATION» FOR MASTERS - Mariia Bratko (Borys Grinchenko Kyiv Metropolitan University, 2022)
The article examines both the theoretical and practical aspects of storytelling as a teaching technology in higher education at the second (master's) level. The benefits of incorporating storytelling into the practice of teaching the course «Leadership in Education» is demonstrated, since telling stories is a relevant tool for leaders at all levels. The content and objectives of the course «Leadership in Education», which is included in the innovative educational program «Corporate Education and Personnel Development» at Borys Grinchenko University of Kyiv, are briefly described. There is a brief theoretical review of current English and Ukrainian scientific works on the subject under consideration. The following functions of storytelling as a teaching technology are distinguished: educational, value-oriented, motivational, educational, developmental, communicative, and mentoring. Methodological recommendations for the creation of a successful story, relating to its structure and required components, are developed. An example of recommendations on the use of storytelling, which the author followed when teaching the course «Leadership in Education» at the second (master's) level of higher education, is given. The recommendations are based on the theoretical generalization of scientific views of scientists and their own pedagogical experience. Based on student feedback, it is concluded that using storytelling in higher education as a technology that improves the efficiency of the educational process is recommended. The study has confirmed the need for a thorough examination of the pedagogical and psychological foundations of storytelling, as well as appropriate teacher training in the use of this technology.